Trinidad and Tobago general election 11 December 2000 : report (Commonwealth Secretariat LondonGB, 2001)
Presents the Group's observations of the relevant aspects of the organisation and conduct of the general election in Trinidad and Tobago.
Keywords: ELECTIONS